2011
DOI: 10.4025/actascibiolsci.v33i2.7228
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variation of attributes from flagellate protozoan community in tropical streams

Abstract: This study verified the existence of longitudinal patterns in species composition, richness, density and biomass of flagellate protozoan in tropical streams and investigated whether the possible zonation patterns are different between two periods of the year. For this, samplings were carried out in three regions from 10 streams, during the summer and winter. The flagellate community may be considered species-rich, because it was represented by 106 taxa, belonging to 8 orders and 1 residual group. The values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…These differences can be related to the climate, latitude and especially to methodological procedures, once these authors have considered only heterotrophic flagellates and the present study considered this community as a whole, evaluating the heterotrophic, mixotrophic and autotrophic fractions. The studies that have considered all fractions (Carlough and Meyer, 1989;Araújo and Godinho, 2008;Camargo and Velho, 2011) presented composition patterns more similar to the observed in this study, with an expressive qualitative contribution of euglenids.…”
Section: Patterns Of Spatial and Seasonal Distribution Of Species Comsupporting
confidence: 84%
See 2 more Smart Citations
“…These differences can be related to the climate, latitude and especially to methodological procedures, once these authors have considered only heterotrophic flagellates and the present study considered this community as a whole, evaluating the heterotrophic, mixotrophic and autotrophic fractions. The studies that have considered all fractions (Carlough and Meyer, 1989;Araújo and Godinho, 2008;Camargo and Velho, 2011) presented composition patterns more similar to the observed in this study, with an expressive qualitative contribution of euglenids.…”
Section: Patterns Of Spatial and Seasonal Distribution Of Species Comsupporting
confidence: 84%
“…In general, this community can be controlled by both biotic and abiotic factors, such as food resource availability, predation pressure, pH, electrical conductivity, dissolved oxygen, trophic state, and climatic seasonality (Pace and Funke, 1991;Arndt, 1993;Samuelsson et al, 2006;Araújo and Godinho, 2008;Camargo and Velho, 2011). Nevertheless, evidences have suggested that in tropical lotic environments flagellates are primarily controlled by seasonal variation of the rainfall regime (Araújo and Godinho, 2008;Camargo and Velho, 2011), which modifies the structure and metabolism of the environment and aquatic communities as well (Cushing and Allan, 2001). On the other hand, the water quality can also influence the distribution of these organisms, as reported by some authors (Jiang and Shen, 2005;Araújo and Godinho, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Camargo and Velho (2011), the success of flagellate protozoa in streams can be attributed to human activities in the region, as some groups are considered indicators of impacted environments because of their preference for environments rich in organic matter (Reynolds and Descy, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have focused on the diverse effects of human activities on these environments (Kühl et al, 2010;Camargo and Velho, 2011;Cunico et al, 2012).…”
Section: Introductionmentioning
confidence: 99%